Analisis Pengaruh Kepuasan Kerja dan Motivasi Terhadap Kinerja Karyawan Dengan Komitmen Organisasional Sebagai Variabel Intervening - Reni Febrianti; Joko Triono (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
The purpose of this research was to analyze the effect of job satisfaction, motivation and organizational commitment on employee performance. The object of research chosen in this study was contract employees at PT. Mutiara Timur Raya. Data was collected through a questionnaire method that was filled independently of 110 respondents / all contract employees in the company using the census method. Measurement of exogenous and endogenous constructs was tested using confirmatory factor analysis (CFA) and the results showed that the full model feasibility test was within the range of expected values. The results of this study prove and give the conclusion that: (1) job satisfaction has a positive and significant effect on organizational commitment, (2) motivation has a positive and significant effect on organizational commitment, (3) job satisfaction has a positive effect on employee performance but not significant, (4) motivation has a positive effect on employee performance but is not significant, (5) organizational commitment has a positive and significant effect on employee performance, and (6) job satisfaction and motivation have a positive and significant effect on employee performance through organizational commitment. Keywords: Organizational culture, job satisfaction, organizational commitment, and employee performance